Endometriomas and Assisted Reproductive Technology - Flyckt, Rebecca; Soto, Enrique; Falcone, Tommaso (Seminars in Reproductive Medicine, 2013)
Endometriomas in the assisted reproductive technology patient present a challenging clinical scenario for the infertility specialist. Although surgical management is often pursued in cases of pain or large cyst diameter, patients without such factors must be counseled regarding surgical versus expectant management. Decisions to pursue surgery must be viewed in the context of potentially decreased ovarian reserve and more difficult stimulation for in vitro fertilization. In this article, three distinct cases are presented along with a summary of the most current literature available to guide clinicians in the optimal management of in vitro fertilization patients with endometriomas.
Keywords: endometriomas; ovarian cystectomy; assisted reproductive technology; ovarian reserve